Evaluating The Application Of The Basic Principles Of Strategic Management Issued By INTOSAI - سليطين, سوما (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research is aimed to evaluate the application of the basic principles of strategic management issued by the International Organization of Supreme Audit Institutions for Financial and Accounting Control in the Central Organization for Financial Control in Syria. The research relied the analytical descriptive approach as a general method As For data Collection by way of questionnaire and personal Interview, As for the research community, it is the strategic planning team in the Central Organization for Financial Control in Syria, in addition to the experienced administrators at all levels in the agency’s branches (Lattakia and Tartous). The most important results of the research have been represented as follows: 1: The Central Organization for Financial Control in Syria applies the basic principles of strategic management issued by INTOSAI, except some items, including the following: The number of members of the strategic management team is few 2: The system for measuring the performance of the agency contains an excessive number of indicators 3: The opinions and observations of employees or representatives are not requested About them during the stages of strategic management. As for the most important recommendations, it is to continue applying the principles of strategic management according to the latest INTOSAI publications and adapting them to suit our Syrian environment. Therefore, in order to implement them, it must do several things, including: Increasing the number of members of the strategic management team commensurate with the burden of their application2 Reducing the number of indicators used in the device performance measurement system 3, a request for opinions and observations Employees of the agency or their representatives during the stages of strategic management